Birkhoff Center of a Quotient of Almost Distributive Fuzzy Lattices (Journal of Informatics and Mathematical Sciences, 2019)
The concept of a fuzzy congruence relation is introduced, and we also prove quotient isomorphism in Almost Distributive Fuzzy lattice.
Keywords: Almost distributive lattice; Almost distributive fuzzy lattice; fuzzy poset; Relatively complemented ADFL; Birkhoff center of an Almost distributive lattice; Birkhoff center of an almost distributive fuzzy lattice